APPROXIMATION OF CONJUGATE DIFFERENTIABLE FUNCTIONS BY THEIR ABEL–POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2009)
We obtain the exact values of upper bounds of approximations of classes of periodic conjugate differentiable functions by their Abel–Poisson integrals in uniform and integral metrics.